Antibacterial Peptide-Based Gel for Prevention of Medical Implanted-Device Infection. - Mihaela Mateescu; Sébastien Baixe; Tony Garnier; Loic Jierry; Vincent Ball; Youssef Haikel; Marie Hélène Metz-Boutigue; Michel Nardin; Pierre Schaaf; Olivier Etienne; Philippe Lavalle (PLoS ONE)
Implanted medical devices are prone to infection. Designing new strategies to reduce infection and implant rejection are an important challenge for modern medicine. To this end, in the last few years many hydrogels have been designed as matrices for antimicrobial molecules destined to fight frequent infection found in moist environments like the oral cavity. In this study, two types of original hydrogels containing the antimicrobial peptide Cateslytin have been designed. The first hydrogel is based on alginate modified with catechol moieties (AC gel). The choice of these catechol functional groups which derive from mussel's catechol originates from their strong adhesion properties on various surfaces. The second type of gel we tested is a mixture of alginate catechol and thiol-terminated Pluronic (AC/PlubisSH), a polymer derived from Pluronic, a well-known biocompatible polymer. This PlubisSH polymer has been chosen for its capacity to enhance the cohesion of the composition. These two gels offer new clinical uses, as they can be injected and jellify in a few minutes. Moreover, we show these gels strongly adhere to implant surfaces and gingiva. Once gelled, they demonstrate a high level of rheological properties and stability. In particular, the dissipative energy of the (AC/PlubisSH) gel detachment reaches a high value on gingiva (10 J.m-2) and on titanium alloys (4 J.m-2), conferring a strong mechanical barrier. Moreover, the Cateslytin peptide in hydrogels exhibited potent antimicrobial activities against P. gingivalis, where a strong inhibition of bacterial metabolic activity and viability was observed, indicating reduced virulence. Gel biocompatibility tests indicate no signs of toxicity. In conclusion, these new hydrogels could be ideal candidates in the prevention and/or management of periimplant diseases.